Pentingnya Pemahaman Tentang Sosial Bagi Anak Panti Asuhan Hanifah III - S, Sutrisno; A, Afrinaldi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Education is basically the right of every child without exception. However, the reality found in the field is that fulfilling children's educational needs is not as easy as imagined. This is because not all children are lucky to be born into a family that is physically and financially capable of meeting all of the child's needs, some children are actually born into families with a life of complete deprivation so they cannot guarantee the fulfillment of all the child's needs and the child's welfare. These limitations encourage children to experience care outside the family. One of the social service institutions that is specifically designed as an alternative to child care is the social care home for children. However, the existence of orphanages is often hit by various issues related to the limitations of orphanage services, such as the absence of a permanent source of funds, limited facilities, and a shortage of professional staff that often accompany the existence of these children's social service institutions. Referring to several research results, it shows that the fulfillment of children's educational rights and needs in orphanages is not optimal because they are often faced with funding problems from irregular donors. On the other hand, children in orphanages also often experience a lack of attention and affection because there are only a few caregivers in orphanages. so that the education of orphaned children is often left behind compared to children their age who are cared for in the family.